2014
DOI: 10.1371/journal.pone.0096547
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Currently Approved Carriers and Adjuvants on the Pre-Clinical Efficacy of a Conjugate Vaccine against Oxycodone in Mice and Rats

Abstract: Vaccination against the highly abused prescription opioid oxycodone has shown pre-clinical efficacy for blocking oxycodone effects. The current study further evaluated a candidate vaccine composed of oxycodone derivatized at the C6 position (6OXY) conjugated to the native keyhole limpet hemocyanin (nKLH) carrier protein. To provide an oxycodone vaccine formulation suitable for human studies, we studied the effect of alternative carriers and adjuvants on the generation of oxycodone-specific serum antibody and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
74
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 39 publications
9
74
0
Order By: Relevance
“…However, OXY-KLH was effective in reducing oxycodone distribution to brain when 2.3 mg/kg oxycodone was administered subcutaneously, a dose similar to the high dose administered intravenously. OXY-KLH also reduced opioid-induced antinociception in the hot-plate assay at this same oxycodone dose given subcutaneously, as previously reported (Pravetoni et al, 2014b). The expected slower absorption of oxycodone into blood after subcutaneous compared with intravenous administration was likely responsible for the increased vaccine efficacy despite the high oxycodone dose.…”
Section: Efficacy Of Vaccines For Opioid Use Disorderssupporting
confidence: 81%
See 2 more Smart Citations
“…However, OXY-KLH was effective in reducing oxycodone distribution to brain when 2.3 mg/kg oxycodone was administered subcutaneously, a dose similar to the high dose administered intravenously. OXY-KLH also reduced opioid-induced antinociception in the hot-plate assay at this same oxycodone dose given subcutaneously, as previously reported (Pravetoni et al, 2014b). The expected slower absorption of oxycodone into blood after subcutaneous compared with intravenous administration was likely responsible for the increased vaccine efficacy despite the high oxycodone dose.…”
Section: Efficacy Of Vaccines For Opioid Use Disorderssupporting
confidence: 81%
“…However, we have previously shown that native KLH and dimer KLH are equally effective as carrier proteins for the development of oxycodone vaccines (Pravetoni et al, 2014b), and in the current study both vaccine formulations elicited similar serum opioid-specific antibody concentrations.…”
Section: Efficacy Of Vaccines For Opioid Use Disorderssupporting
confidence: 66%
See 1 more Smart Citation
“…33,34 The strength of this approach is that very rare antigen-specific B and T cells are detected prior to, or shortly after immunization. [35][36][37][38][39] To date, this approach has been used to test the effect of hapten structure, 40,41 adjuvant, 42 or host genetics 42 on the B cell response to vaccines for SUD. This strategy has also been used to study the relationship between antigen-specific B and T cells and individual variability in post-immunization Ab titers, or efficacy against drug distribution and drug-induced behavior in mice.…”
Section: Pre-clinical Developmentmentioning
confidence: 99%
“…[90][91][92] To identify the most promising carrier suitable for translation of a vaccine against oxycodone and hydrocodone, BSA, decamer and dimer KLH, TT, and a TT-derived peptide were tested. 40,42,43,[74][75][76]93 To develop vaccines for treatment of methamphetamine abuse, for which no therapies exist, immunogens containing either native or dimer KLH, or TT, showed promising pre-clinical efficacy in blocking distribution of methamphetamine to the brain and blocking a variety of methamphetamine-induced behaviors, including intravenous self-administration. [94][95][96][97][98] Other carrier proteins have adjuvant-like properties, such as the well-characterized CRM 197 .…”
Section: Pre-clinical Developmentmentioning
confidence: 99%